Financial support from the family network and illegal immigration - Slobodan Djajić (Graduate Institute of International and Development Studies, 2014)
Barriers to immigration of low-skilled workers from developing countries into the advanced countries prevent many potential migrants from leaving their countries of origin. With very low home-country wages in relation to the cost of undocumented migration, the opportunity to migrate often hinges on becoming indebted to a human smuggling organization or family and friends. This paper examines the conditions under which migration is optimal for an individual who lacks liquid assets, with a focus on alternative options for financing migration costs. One is by accumulating the required amount of savings out of source-country income, with or without financial support from the family or social network. The other is debt-bonded migration, which involves borrowing from a smuggling organization and paying o the loan while working in the host country. I find that greater financial support from the family network increases the attractiveness of debt-bonded relative to self-financed migration.
Keywords: F22; J61; 330; liquidity constraints; debt-bonded labor; illegal immigration; financial support